Right to Clean Water: Lake Xochimilco, Mexico City - Arévalo, Ana Luisa González (Archives of Business Research, 2022)
Lake Xochimilco is in the region of the same name in Mexico City. The objective of this article is to tell about the serious contamination that this body of water presents. In the first part, is the theoretical elements. They are addressed about the right of any human being to clean water. Later, the geographical factors are mentioned about the location of Lake Xochimilco. Yet a comparison of economically important elements is made. Such as economic units, the value of production, the employed personnel, the remunerations of the other districts that make up Mexico City. Likewise, the elements of a social nature such as the total population in a situation of poverty at Xochimilco and the other demarcations. In the end the contamination of this lake is described, some proposals are presented to gradually solve the pollution of this place through good governance, which is not only the result of good governance, but of an interaction of government organization, the private sector and civil society.